Stimulation of resistance genes and antioxidant enzymes in lettuce by nano metal oxides against root rot caused by Rhizoctonia solani - Tarek A. Essa; Nashwa A. H. Fetyan; Tamer M. Salem; Nazih Y. Rebouh; Abdelaziz Kishk; Mohamed H. Abdelfattah (PLoS ONE, 2025)
Root rot, caused by Rhizoctonia solani L., is becoming an increasing issue for lettuce. Nanoparticles (NPs) are emerging as a promising approach for managing biotic stress, offering advantages surpassing traditional control methods. This studyaimed to evaluate the effectiveness of silicon dioxide (SiO2), copper oxide (CuO), and gamma iron oxide (γFe2O3) nanoparticles in inducing systemic resistance (SR) in lettuce against R. solani by examining the molecular response, particularly the expression of pathogenesis-related and stress-regulatory genes. Additionally, assessed total protein contents, photosynthetic pigments, Hydrogen peroxide (H2O2), malondialdehyde (MDA), and antioxidant enzymes. The results demonstrated that NPs significantly reduced basal rot symptoms and decreased the Area Under the Disease Progress Curve (AUDPC) values. Treated plants also showed increased protein and chlorophyll levels compared to untreated controls. Infected plants showed higher levels of lipid peroxidation (MDA and H2O2). However, treatments with SiO2 and γFe2O3 effectively mitigated the oxidative stress. All NPs enhanced carotenoid content and antioxidant enzyme activity (superoxide dismutase [SOD], catalase [CAT], and ascorbate peroxidase [APX]), with γFe2O3 being the most effective. Importantly, NPs induced expression of pathogenesis-related genes, PR1, PR3, and PR4, as well as the Ethylene-Responsive Transcription Factor 1A gene (ERT1). The upregulation of these genes was correlated with reduced disease symptoms and improved physiological status, indicating that enhanced gene expression contributed to the observed systemic resistance. This is the first study to report the fatty acid hydroperoxide lyase (FHL) gene activation in lettuce treated with CuO, γFe₂O₃, and SiO₂ nanoparticles against R. solani. These findings suggest that NPs are promising for managing R. solani in lettuce, applicable in both greenhouses and fields by enhancing systemic resistance.